Infections in systemic lupus erythematosus: A study of incidence and risk factors in 100 patients from western India - Ankan Jha; Tridip Das; Sunilkumar Rajmani Singh; Jyotsna Oak (Indian Journal of Rheumatology)
Aim: The present study was conducted to evaluate the incidence and characteristics of infections in patients of systemic lupus erythematosus (SLE) and determine the risk factors for infection. Materials and Methods: This is a prospective, observational study carried out at a single-center, tertiary care hospital. The study included all adult SLE patients diagnosed as per the revised American College of Rheumatology (ACR) criteria from January 2015 to October 2019. Episodes of infection and pathogens isolated were recorded. Results: A total of 100 patients with SLE were evaluated (94 females and 6 males). Forty-seven (47%) patients suffered from 54 episodes of infection. Urinary tract infections were most common (31.48%), followed by skin and mucous membrane (27.78%). Escherichia coli (E. coli) was the most common organism isolated in 9 (16.8%) cases. Tuberculosis was seen in 6 (11.1%) patients. Forty-three (79.6%) patients had a SLE disease activity index score of more than 5 at the time of infection. Significant risk factors for infection included use of prednisolone, prednisolone dose higher than 10 mg, use of cyclophosphamide within the preceding 3 months of infections, use of other immunosuppressive agents, and leukopenia. Renal lupus and presence of comorbidities did not have a significant association with occurrence of infections. The relative risk of infections in SLE patients was 4.7 compared to non SLE controls. Conclusion: Patients of SLE are at increased risk for various infections. Management of SLE needs vigilance for infection and judicious use of immunosuppressive drugs.